Prevalence of Congenital Heart Disease among Children in Khorramabad (West of Iran) - Nezami, Alireza; Heidari, Ghobad; Tarhani, Fariba; Kariminia, Masoumeh (Cardiovascular & Haematological Disorders - Drug Targets, 2021)
Aims: Congenital heart disease is among the most common congenital anomalies in pediatrics. The aim of this study was to evaluate the prevalence of congenital heart disease in children in Khorramabad, Iran. Methods: This is a descriptive-cross sectional study where all the children diagnosed with congenital heart disease by echocardiography were enrolled to the Shahid Madani Hospital. Patient information was collected by means of a questionnaire. Of 1600 children who underwent cardiac counseling, 9.75% presented congenital heart disease. These were most prevalent among the children of 0-28 days of the age (14.7%) and least in children aged 1 month-1 year. According to this study, atrial (20.3%) and ventricular septal defect (10.5%) were the most common heart defects, respectively. Among signs and symptoms of cardiac disease, 49.1% of children had cyanosis, 89.7% with increased CT (cardiothoracic)-ratio, and 82.7% of had heart murmur. Congenital heart disease was more prevalent in male infants (58%) and 6.6% patients had heart failure and 1.4% had other congenital conditions, such as Down syndrome. Results: According to our findings, atrial and ventricular septal defects are the most common congenital heart anomalies, respectively, in pediatric patients in Khorramabad.
Keywords: echocardiography